Time-varying effects of oil supply shocks on the U.S. economy - Christiane Baumeister; Gert Peersman (Bank of Canada, 2012)
We use vector autoregressions with drifting coefficients and stochastic volatility to investigate how the dynamic effects of oil supply shocks on the U.S. economy have changed over time. We find a substantial decline in the short-run price elasticity of oil demand since the mid-eighties. This finding helps explain why an oil production shortfall of the same magnitude is associated with a stronger response of oil prices and more severe macroeconomic consequences over time, while an oil price increase of the same magnitude is associated with a smaller decline in oil production and smaller losses in U.S. output in more recent years. We also show that oil supply shocks more recently account for a smaller fraction of the variability of the real price of oil, implying a greater role for oil demand shocks. Notwithstanding this time variation, the overall cumulative effect of oil supply disruptions on the U.S. economy has been modest. Oil supply shocks contributed to some extent to the 1991 recession and slowed the economic boom of 1999 - 2000, but they do not explain other U.S. recessions nor do they help explain the Great Inflation of the 1970s and early 1980s.
Keywords: E31; E32; Q43; 330; Econometric and statistical methods; International topics